Nightmares as predictors of suicide: an extension study including war veterans - Nils Sandman; Katja Valli; Erkki Kronholm; Erkki Vartiainen; Tiina Laatikainen; Tiina Paunio (Springer Nature, 2022)
Nightmares are intensive dreams with negative emotional tone. Frequent nightmares can pose a
serious clinical problem and in 2001, Tanskanen et al. found that nightmares increase the risk of suicide.
However, the dataset used by these authors included war veterans in whom nightmare frequency - and
possibly also suicide risk - is elevated. Therefore, re-examination of the association between nightmares
and suicide in these data is warranted. We investigated the relationship between nightmares and
suicide both in the general population and war veterans in Finnish National FINRISK Study from the
years 1972 to 2012, a dataset overlapping with the one used in the study by Tanskanen et al. Our data
comprise 71,068 participants of whom 3139 are war veterans. Participants were followed from their
survey participation until the end of 2014 or death. Suicides (N = 398) were identified from the National
Causes of Death Register. Frequent nightmares increase the risk of suicide: The result of Tanskanen et al.
holds even when war experiences are controlled for. Actually nightmares are not significantly associated
with suicides among war veterans. These results support the role of nightmares as an independent risk
factor for suicide instead of just being proxy for history of traumatic experiences.